The impact of policy diffusion on optimal emission taxes - Peter Michaelis; Thomas Ziesemer (Universität Augsburg, Institut für Volkswirtschaftslehre, 2012)
We incorporate the process of policy diffusion (i.e. the uncoordinated dissemination of policies among countries) into a probabilistic two-country-model of strategic environmental policy. Contrary to the usual setting with simultaneous decision making we consider the impact of sequential decision making: In the first step the domestic government introduces an emission tax, in the second step policy diffusion occurs with a certain probability and in the third step the firms decide on output quantities. Within this framework we analyze how the prospect of policy diffusion, motivated by a higher damage parameter in the domestic country, influences the optimal domestic emission tax. We show that if the damage parameter in the foreign country is sufficiently high policy diffusion will occur which leads to higher tax rates and higher welfare compared to the equilibrium resulting from simultaneous decision making. Moreover, we show that an increase in the domestic tax rate also increases the probability that the foreign country adopts the tax policy.
urn:nbn:de:bvb:384-opus4-711015
Keywords: F18; Q55; Q58; 330; strategic environmental policy; emission tax; policy diffusion; sequential decision-making